An integrated pedagogical approach for distance learning courses: curriculum, ICT and management - Martins, Joberto S. B. (2006)
Distance learning courses need intensive planning that, in turn, requires the integration of knowledge and expertise in different areas and levels such as curriculum, ICTs and course management. This paper presents an integrated approach for distance learning course planning that derives from pedagogical research the basic directives to integrate the process variables such as curriculum, ICT options and management. It is argued that distance learning projects always have some research activity involved, since the operation model construction always requires the identification of course characteristics and specificities in order to face the challenges imposed by this teaching method and take advantage of ICT technologies in a specific socioeconomical context. In practical terms, course implementation is focused on pedagogical-driven decisions based on a flexible curriculum model suitable for different implementation scenarios and course characteristics. The integrated approach has been used in various high capillary courses (humanities, mathematics, others) with limited ICT resources